Differential colocalization of estrogen receptor β (ERβ) with oxytocin and vasopressin in the paraventricular and supraoptic nuclei of the female rat brain: An immunocytochemical study - Alves, Stephen E. (The National Academy of Sciences, 1998)
Evidence exists for the localization of the newly identified estrogen receptor β (ERβ) within the rat paraventricular nucleus (PVN) and supraoptic nucleus (SON), regions which lack ERα. Presently, we investigate whether ERβ-like-immunoreactivity (-ir) is found within cells of several major neuropeptide systems of these regions. Young adult Sprague–Dawley rats were ovariectomized (OVX), and 1 week later half of the animals received estradiol-17β (E). Dual-label immunocytochemistry was performed on adjacent sections by using an ERβ antibody, followed by an antibody to either oxytocin (OT), arginine-vasopressin (AVP), or corticotropin releasing hormone. Nuclear ERβ-ir was identified within SON and retrochiasmatic SON, and in specific PVN subnuclei: medial parvicellular part, ventral and dorsal zones, dorsal and lateral parvicellular parts, and in the posterior magnocellular part, medial and lateral zones. However, the ERβ-ir within magnocellular areas was noticeably less intense. OT-/ERβ-ir colocalization was confirmed in neurons of the parvicellular subnuclei, in both OVX and OVX+E brains (≈50% of OT and 25% of ERβ-labeled cells between bregma −1.78 and −2.00). In contrast, few PVN parvicellular neurons contained both AVP- and ERβ-ir. As well, very little overlap was observed in the distribution of cells containing corticotropin releasing hormone- or ERβ-ir. In the SON, most nuclear ERβ-ir colocalized with AVP-ir, whereas few OT-/ERβ-ir dual-labeled cells were observed. These findings suggest that estrogen can directly modulate specific OT and AVP systems through an ERβ-mediated mechanism, in a tissue-specific manner.